The administration of pro re nata medication by mental health nurses: a thematic analysis. - Doyle, Louise (My University, 2019)
Pro re nata (PRN) medication is medication administered by nurses as required commonly in response to a patient’s symptoms or behaviour including insomnia, agitation or anxiety. There is a paucity of research around the process of PRN administration in mental health settings in Ireland and international evidence suggests inconsistencies in practices. This study aimed to explore the process of PRN medication administration by mental health nurses. Using a qualitative descriptive design, semi-structured interviews were undertaken with 19 mental health nurses in three acute inpatient units in one mental health service in Ireland. Most participants reported undertaking an assessment of the patient before administering PRN medication; however, many also reported having observed incidents of poor practice. There was evidence of some interdisciplinary sensitivities around instructions regarding the use of PRN medications between doctors who prescribed them and nurses who dispensed them. A need for service improvements were also identified including the use of alternative strategies to PRN use such as de-escalation techniques and education around psychopharmacology. PRN medication is commonly used in mental health settings; however, this study suggests that there is potential for improvement in relation to how it is prescribed and administered. Overuse of PRN medication has been associated with increased morbidity. Mental health nurses are required to carefully consider whether PRN medication is warranted in the first instance and how its use might impact on patients.
PUBLISHED
Keywords: Pro re nata; Psychotropic medication; Mental health nurses; Inpatient medication administration